Autophagic activation of IRF‐1 aggravates hepatic ischemia–reperfusion injury via JNK signaling. Issue 1 (11th February 2021) - Li, Shipeng; He, Jindan; Xu, Hongwei; Yang, Jiaxing; Luo, Yutian; Song, Wenyue; Qiao, Bingbing; Zhang, Haiming
Abstract: Increasing evidence has accrued indicating that autophagy is associated with hepatic ischemia–reperfusion injury (IRI). This report demonstrates that interferon regulatory factor‐1 (IRF‐1) was upregulated in response to hepatic IRI and was associated with autophagic activation. As a result of these processes, there is an aggravation of liver damage, effects that can be offset by IRF‐1 depletion. In addition, these effects of IRF‐1 are associated with JNK pathway activation followed by increases in Beclin1 protein levels. This JNK‐induced autophagic cell death then leads to cell failure, and plays an important role in liver function damage. We conclude that IRF‐1 activates autophagy through JNK‐mediated autophagy. Accordingly, these findings indicating that the IRF‐1/JNK pathway activates autophagy to exacerbate liver IRI in this mouse model may provide new insights into novel protective therapies for hepatic IRI. Abstract : The expression of interferon regulatory factor‐1 (IRF‐1) is related to the high autophagy activity and aggravates the liver damage, which is offset by IRF‐1 depletion in vivo or in vitro. IRF‐1 can activate autophagy to aggravate hepatic ischemia–reperfusion via regulating JNK pathway.